2017
DOI: 10.1093/nar/gkx556
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-cell variability and robustness in S-phase duration from genome replication kinetics

Abstract: Genome replication, a key process for a cell, relies on stochastic initiation by replication origins, causing a variability of replication timing from cell to cell. While stochastic models of eukaryotic replication are widely available, the link between the key parameters and overall replication timing has not been addressed systematically. We use a combined analytical and computational approach to calculate how positions and strength of many origins lead to a given cell-to-cell variability of total duration o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…We also demonstrated that after transcription inhibition, S phase duration remained the same, at least after a short period ( Figure 6D). This result confirms the robustness of S phase duration, as previously suggested by other studies (47,74). Several studies have demonstrated the activation of dormant origins following replication stress to ensure the completion of DNA replication near stalled or collapsed 26 replication (6,14,(75)(76)(77).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also demonstrated that after transcription inhibition, S phase duration remained the same, at least after a short period ( Figure 6D). This result confirms the robustness of S phase duration, as previously suggested by other studies (47,74). Several studies have demonstrated the activation of dormant origins following replication stress to ensure the completion of DNA replication near stalled or collapsed 26 replication (6,14,(75)(76)(77).…”
Section: Discussionsupporting
confidence: 90%
“…Based on these features and considering that the precise S phase duration estimated previously ( Figure 1) is robust, as proposed for other cell types (21,47), simulations with our stochastic computational models suggest that the presence of replication-transcription conflicts might lead to an increase in origin firing, which in turn helps to maintain the robustness of the S phase duration (Figure 3, Supplementary Table S2). Analyzed together, these simulations suggest the presence of a mechanism responsible for a decrease in the mean IOD estimated under standard conditions, making the parasites fire a pool of origins greater than the minimum required to complete S phase.…”
Section: Discussionsupporting
confidence: 71%
“…These apparently stochastic differences in cell-cycle durations were originally attributed exclusively to the G1 phase 13 . However, more recent studies in multiple cell types have revealed that S and G2 also contribute significant variability to total cell cycle duration 3,14,15 . Collectively, these studies have revealed that differences in cell cycle durations are an inherent property of individual cells and raise the fundamental question of how these durations are determined.Over the past 50 years, multiple models have been put forth to explain the differences in cell cycle phase durations among individual cells.…”
mentioning
confidence: 99%
“…As functional properties, we considered the efficiency and the characteristic firing time of each individual origin and that of its closest neighboring origin along the chromosomes. We used a stochastic mathematical model to infer origin firing rates from the fit to our replication timing data and derived the efficiency and firing time of each individual origin in the 10 Lachancea genomes from running the model 14 .…”
Section: The Loss Of An Active Replication Origin Depends On Its Neigmentioning
confidence: 99%
“…Mathematical modeling of such replication timing data gives access to the stochastic firing components of each individual origin 10,[12][13][14] . First, each replication origin has a given probability of activation, named efficiency, which represents the proportion of the cells in a population in which the origin actively fires.…”
Section: Introductionmentioning
confidence: 99%